2016
DOI: 10.1590/0037-8682-0415-2015
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral fever response in Rhodnius prolixus (Reduviidae: Triatominae) to intracoelomic inoculation of Trypanosoma cruzi

Abstract: Introduction: Behavioral fever is a response to infections with microorganisms observed in some poikilothermic animals. Rhodnius prolixus is involved in the transmission of two parasites: Trypanosoma cruzi (pathogenic for humans and transmitted in feces) and Trypanosoma rangeli (non-pathogenic for humans, pathogenic for Rhodnius and transmitted by the bite of an infected individual). Only T. rangeli is found in the hemolymph of Rhodnius as it travels to the salivary glands. Methods: To study vector-parasite in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…For instance, Botto-Mahan [61] found that T. cruzi infection delays the development and reduces survival rates in the triatomine Mepraia spinolai . Studies more closely related to our work found that T. cruzi reduced the survival of the triatomine Rhodnius prolixus , but only at 20 °C and 30 °C [31, 34]. In our case, the insects were more affected by the Chilpancingo strain than by the Morelos strain.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…For instance, Botto-Mahan [61] found that T. cruzi infection delays the development and reduces survival rates in the triatomine Mepraia spinolai . Studies more closely related to our work found that T. cruzi reduced the survival of the triatomine Rhodnius prolixus , but only at 20 °C and 30 °C [31, 34]. In our case, the insects were more affected by the Chilpancingo strain than by the Morelos strain.…”
Section: Discussionsupporting
confidence: 73%
“…It is worth noting, however, that despite the strong effect of higher temperatures on reduced survival, this does not mean that the triatomine bugs do not rely on a fever response to deal with pathogens. Actually, other studies have found that triatomines show fever responses when sick [34]. It would be interesting to see whether M. pallidipennis bugs increase their fitness when allowed to choose ambient temperatures while facing different T. cruzi isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other animals, the immune system of triatomines consists of cellular and humoral components that respond to pathogens and parasites, 52–54 also including behavioural fever responses. 55 Cellular components have only been found in the hemolymph and not in any section of the intestine. If viruses, bacteria, fungi and parasites gain access to the intestine, the humoral immunity is activated via the immune deficiency (IMD), Toll and JAK-STAT pathways 52 , 56 that induce the production of different antimicrobial peptides (eg, lysozymes, defensins, prolixin, prophenoloxidase cascade), unidentified bacteriolytic compounds and antimicrobial molecules (eg, nitric oxide).…”
Section: Triatominesmentioning
confidence: 99%
“…Peterson et al ., 2016; Cordero-Montoya et al ., 2019; reviewed by de Oliveira et al ., 2018). This cost could lead the insect to enhance its immune response (de Fuentes-Vicente et al ., 2016), removing up to 80% of the parasites within hours after ingesting infected blood (Elliot et al ., 2015; Hinestroza et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%